Sastra dan Masyarakat: Fenomena Ambyar pada Lirik Lagu Didi Kempot - Ferdian Achsani (Institut Agama Islam Negeri Curup, 2019)
Didi Kempot or the father of a national heartbreak may already be familiar to the ears of the people of Indonesia, even abroad, especially Suriname and Belanda. The emergence of Didi Kempot revived music campursari which had long been vacuum and was once again accepted by the public from all walks of life. This distinctive mixed singer with mellow nuances is now being loved by the public, especially young people. This study aims to describe the form of ambyar phenomenon in the lyrics of the song Didi Kempot with the public. This research is a qualitative descriptive type, using content analysis as a data analysis technique. Data collection is carried out by conducting documentation studies. Data validity test is done by using triangulation of research results showing that Didi Kempot's lyrics represent the feelings of ambyar young people in having a love relationship such as being cheated, broken promises, disappointed, and harbored a longing. The background of this ambyar phenomenon is due to a lack of concern or commitment in establishing relationships, economic factors, establishing long-distance relationships, remembering memories with ex, etc. Keywords: song lyrics, ambyar, literature and society.